Heat Integration Analysis of the Pre-Design Stage of an Ethyl Acetate Production Process using Pinch Technology - Dhiva Pooja Sabila; Dyaning Nur Wijayanti; Abigaiell Endrian Pawesty; Gesti Andini (Journal of Vocational Studies on Applied Research, 2026)
Industrial heat exchanger networks often exhibit suboptimal energy utilization because of limited heat integration between process streams. This study aims to optimize a heat exchanger network (HEN) through the application of pinch analysis based on the initial process flowsheet. Hot and cold stream data, including inlet temperature, outlet temperature, and heat load, were first analyzed using Microsoft Excel and subsequently processed using the Heat Integration Network Tool (HINT). Pinch analysis was conducted by constructing composite curves to identify the pinch point, which represents the thermodynamic constraints of the system. Based on the analysis results, a redesigned heat exchanger network was developed in accordance with pinch principles, namely, the elimination of heat transfer across the pinch and the enhancement of internal heat recovery. The results demonstrate that the application of pinch analysis leads to a more efficient heat exchanger network configuration and reduces the reliance on external heating and cooling utilities compared with the initial system.